Stealing Obedience : Narratives of Agency and Identity in Later Anglo-Saxon England - O'Brien O'Keeffe, Katherine, 1948- (Book collections on Project MUSE., 2012)
Katherine O'Brien O'Keeffe looks at Benedictine monasticism through the writings of AElfric, Anselm, Osbern of Canterbury, and Goscelin of Saint-Bertin, as well as liturgy, canon and civil law, chronicle, dialogue, and hagiography, to analyse the practice of obedience in the monastic context. Stealing Obedience brings a highly original approach to the study of Anglo-Saxon narratives of obedience in the adoption of religious identity."--Pub. desc.